Farmers' willingness to contract switchgrass as a cellulosic bioenergy crop in Kansas - Fewell, Jason E.; Bergtold, Jason S.; Williams, Jeffery R. (My University, 2016)
Farmers' adoption of cellulosic biofuel feedstock enterprises plays an important role in the future of agriculture and the renewable fuels \industry. However, no set markets currently exist for bioenergy feedstocks outside of very localized geographic locations and farmers may be reluctant to produce the feedstocks without contracts that help mitigate uncertainty and risk. This study examines farmers' willingness to grow switchgrass under contract using a stated choice approach. Data were collected using an enumerated survey of Kansas farmers and analyzed using latent class logistic regression models. Farmers whose primary enterprise is livestock are less inclined to grow switchgrass. Shorter contracts, greater harvest flexibility, crop insurance, and cost-share assistance increase the likelihood that farmers will grow switchgrass for bioenergy production.
Keywords: Cellulosic Biofuel; Farmer Adoption; Latent Class; Stated Choice Survey; Switchgrass